Rancang Bangun Sistem Manajemen Akademik Prodi Teknik Informatika - Indi Ramadhani Sitorus (PT. Hasba Edukasi Mandiri, 2025)
The development of information technology has encouraged educational institutions, including universities, to integrate digital systems in supporting academic activities. However, in the Informatics Engineering Study Programme at Asahan University, the process of applying for practical work (KP) is still done manually. This results in inefficiency and limitations in serving students, especially for those who live far from campus. This research aims to design an online-based academic management system to digitalise the practical work application process. With a system design approach that involves needs analysis, as well as user interface design, this system is designed to facilitate students in registering practical work places and applying for supervisors without having to attend directly to campus. The result of this research is a system design that is more efficient, structured, and transparent, which is expected to improve the quality of academic services in the Informatics Engineering Study Programme at Asahan University. The implementation of this system in the future is expected to simplify the administrative process and support the modernisation of campus academic data management.